Variability of power output during 40-km outdoor time-trial cycling performances - Davison, R. C.; Smith, M. F.; Coleman, D. A.; Baler, J.; Bird, S. R. (Medicine & Science in Sports & Exercise, 2000)
A majority of cyclists use a target heart rate during time trials to judge pace or effort intensity. There is little information that shows how heart rate monitoring affects power output. Trained cyclists (N = 8) completed a maximal aerobic power test and complete three outdoor 40-km time-trial performances. During the time-trials, Ss could only view heart rate, distance covered, and elapsed time. Data were collected for each quarter of the time-trials. Maximal power was significantly higher in the first quarter of the time-trials than in the other three quarters. It was also significantly higher in the third quarter compared to the fourth. Using a heart rate monitor to judge pace resulted in power levels that were too high and could not be sustained for the time-trial duration. This contradicts the advocacy of even velocity pacing suggesting that heart rate is not a good indication of effort intensity or performance power. Implication. Heart rate should not be used to indicate pacing during an extended endurance performance.